1973
DOI: 10.1021/bi00740a012
|View full text |Cite
|
Sign up to set email alerts
|

Photoregulation of biological activity by photochromic reagents. Inactivators of acetylcholinesterase

Abstract: Three photochromic reagents were synthesized and examined for their ability to inactivate acetylcholinesterase.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
1
2

Year Published

1975
1975
2016
2016

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(17 citation statements)
references
References 12 publications
1
13
1
2
Order By: Relevance
“…The molecule is neither planar nor symmetrical (20,21). The two benzene rings are in planes at an angle of 530 from one another.…”
Section: Commentmentioning
confidence: 97%
“…The molecule is neither planar nor symmetrical (20,21). The two benzene rings are in planes at an angle of 530 from one another.…”
Section: Commentmentioning
confidence: 97%
“…A number of researchers have successfully illustrated the concept of using an existing drug scaffold and then modifying it with a photoswitch to alter the drug's ability to interact with its target [35][36][37][38][39][40][41][42][43][44]. This concept generally involves using the changes that occur to the structure and overall geometry of the photoswitch or linkage distance in the case of two binding sites to regulate activity.…”
Section: Drug-inspired Small Molecule Inhibitorsmentioning
confidence: 99%
“…Cis-trans-photostereoisomerization of azocompounds was also used by Erlanger with co-workers (Bieth et al, 1969(Bieth et al, , 1970 for reversible regulation of the catalytic activity of acetylcholinesterase. N-p-phenylazophenyltrimethylammonium chloride (111) and N-p-phenylazophenylcarbamylcholine iodide (IV), competitive inhibitors of c1--N=N -m H this enzyme, exist in cis-and trans-forms capable of photochemical interconversion, for example:…”
Section: Principle Ementioning
confidence: 99%
“…As noted above, Erlanger and co-workers worked with irreversible (Kaufman et a/., Bieth et al, 1969Bieth et al, , 1973 and reversible (Bieth et al, 1969(Bieth et al, , 1970 photochromic inhibitors for acetylcholinesterase; under the action of light one can change the ratio of the trans-and cis-isomers of the inhibitor and, by using their different reactivity towards the enzyme, the degree of inhibition of acetylcholinesterase. It was demonstrated that the procedure is good for regulating the potential difference across the excitable membrane of the monocellular electroplax of Electrophorus.…”
Section: Principle Ementioning
confidence: 99%